2021
DOI: 10.1177/21501327211008448
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Resilience, and Coping of Healthcare Workers during the COVID-19 Pandemic

Abstract: Objective To estimate the health care workers (HCWs) self-reported stress, resilience, and coping during the COVID-19 pandemic, and to determine inter-professional differences. Participants and Methods An email survey was sent to 474 HCW at a Midwestern HealthCare facility between April 9, 2020 and April 30, 2020. A total of 311 (65.6%) responses were received by May 31, 2020. The survey utilized 3 validated instruments: Perceived Stress Scale (PSS), Brief Resilience Scale (BRS), Brief Resilience Coping Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 30 publications
9
53
0
10
Order By: Relevance
“…Our results confirmed our first hypothesis, which posited that nurses’ perceived stress was positively correlated with symptoms of anxiety and depression. Similar to other studies, our analyses found that self-reported perceived stress correlated significantly with psychopathology [ 36 , 37 ], suggesting that nurses who perceived a high level of stress also perceived more symptoms of anxiety and depression. Remarkably, the levels of wellbeing among nurses during COVID-19, were even lower than among patients in the Spanish community mental health setting [ 21 ], and were lower than previous studies among nurses before and during COVID-19 [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our results confirmed our first hypothesis, which posited that nurses’ perceived stress was positively correlated with symptoms of anxiety and depression. Similar to other studies, our analyses found that self-reported perceived stress correlated significantly with psychopathology [ 36 , 37 ], suggesting that nurses who perceived a high level of stress also perceived more symptoms of anxiety and depression. Remarkably, the levels of wellbeing among nurses during COVID-19, were even lower than among patients in the Spanish community mental health setting [ 21 ], and were lower than previous studies among nurses before and during COVID-19 [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…At the same time, resilience indicators (hardiness, vigor) and self-efficacy were found to be protective factors for good mental health outcomes [ 88 ]. As pointed out from previous research [ 89 ] we found some differences between different categories of healthcare professionals, with nurses experiencing less resilience and more occupational stress [ 65 ]. In our view, this may be partly related to the tremendous workload of nursing professionals in caring for COVID-19 patients, who have demanding needs (e.g., pronation in ICU).…”
Section: Discussionmentioning
confidence: 64%
“…Through resilience, emotion-focused strategies were negatively related to psychological distress directly and indirectly in a sample of Spanish nurses [ 42 ]. Resilience was negatively correlated with depression, stress and anxiety [ 44 , 46 , 54 , 65 , 68 , 71 ]. Age, work experience and level of education had a significant positive correlation with nurses’ resilience score [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Germany, the pandemic has affected more than 3.5 million people by now and has led to at least 86,000 deaths [ 2 ]. Apart from causing considerable acute disease burden and mortality, the COVID-19 pandemic has also significant psychological consequences, causing anxiety, depression, sleeping disorders or physical symptoms including headaches, temporomandibular disorders or back pain [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%